2018
DOI: 10.2147/ndt.s188340
|View full text |Cite
|
Sign up to set email alerts
|

Possible association of Firmicutes in the gut microbiota of patients with major depressive disorder

Abstract: BackgroundGut microbiota can affect human behavior and mood in many ways. Several studies have shown that patients with depression were also accompanied with gut microbiota disorder, in which Firmicutes are related to the protective function of intestinal barrier. In this study, we explore the changes and effects of Firmicutes in the patients with major depressive disorder (MDD).MethodWe recruited 54 subjects, including 27 patients with MDD. Fecal samples were collected for identification by 16S rRNA sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
145
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(194 citation statements)
references
References 46 publications
20
145
5
Order By: Relevance
“…In our study patients with PPD had a lower alpha diversity compared with the normal population. Similar to our results, Huang [13] reported that the alpha diversity indices of major depressive disorder were lower than healthy controls. In other studies [14,15], different results have been presented.…”
Section: Discussionsupporting
confidence: 91%
“…In our study patients with PPD had a lower alpha diversity compared with the normal population. Similar to our results, Huang [13] reported that the alpha diversity indices of major depressive disorder were lower than healthy controls. In other studies [14,15], different results have been presented.…”
Section: Discussionsupporting
confidence: 91%
“…28 They have documented roles in fermentation of carbohydrates as well as lipid droplet formation for energy storage. 29,30 In our dendrogram we observe the same trend with a considerable number of our isolates grouped into the Firmicute phylum ( Figure 2 ). Of the Firmicutes isolated, B. subtilis was the most abundant isolate in this phylum.…”
Section: Discussionsupporting
confidence: 77%
“…It typically observed that low alpha-diversity is a hallmark of dysbiosis and represents "worse" health (Yatsunenko et al, 2012). However, the literature on alpha-diversity in psychiatric populations has been mixed (e.g., no differences Shen et al, 2018;Coello et al, 2019;Painold et al, 2019;Zheng et al, 2016;Naseribafrouei et al, 2014;Chen et al, 2018), decreased (Zheng et al, 2019;Huang et al, 2018;Ma et al, 2020), and increased (Zhu et al, 2020;Jiang et al, 2015). A recent meta-analysis of the gut microbiota in major depressive disorder revealed no difference in alpha-diversity between patients and NCs (Sanada et al, 2020).…”
Section: Discussionmentioning
confidence: 99%